Trust of Information Technology Governance in High School Institution (HSI): A Conceptual Framework - Resad, Setyadi; Aedah, Abd Rahman; A'ang, Subiyakto; Anwar, Fattah (2021)
This study aims to build a conceptual framework for previous research. This research is related to High School Institution (HSI) readiness and usability for using the Information Technology Governance Trust (ITGT) model. The findings based on the literature review provide the initial construction and subsequently become a model conceptual framework. The comparison results with previous research indicate an influence between readiness and usability to user trust when implementing Information Technology Governance (ITG.) in an institution. The impact was identified through past literature, namely assessing the relationship between the Readiness domain and the Usability domain towards ITG. By testing HSI users, a trust will appear through testing to develop a framework model research